2015
DOI: 10.1016/j.jfma.2013.10.023
|View full text |Cite
|
Sign up to set email alerts
|

HBV-DNA level at 6 months of entecavir treatment predicts HBeAg loss in HBeAg-positive chronic hepatitis B patients

Abstract: On-treatment complete virological response at Month 6 is a favorable factor predictive of HBeAg loss at 2 years of entecavir therapy. Therefore, measurement of serum HBV-DNA level at 6 months of entecavir therapy is optimal to predict HBeAg loss at 2 years of therapy in HBeAg-positive CHB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…While our results coincide with data from Far east and Middle of Asia [18][19][20][21][22]. Chang et al from Taiwan, showed in their 5 year follow up study of 146 Entecavir treated patients that 94% (88/94) had HBV-DNA <300 copies/mL and 80% (78/98) had normalized ALT levels [19].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While our results coincide with data from Far east and Middle of Asia [18][19][20][21][22]. Chang et al from Taiwan, showed in their 5 year follow up study of 146 Entecavir treated patients that 94% (88/94) had HBV-DNA <300 copies/mL and 80% (78/98) had normalized ALT levels [19].…”
Section: Discussionsupporting
confidence: 91%
“…These findings coincide with Ting and his colleagues who 23% achieved HBeAg sero-conversion and 1.4% HBsAg sero-conversion during the study [19]. Also similar results were shown by Cheng-Yuan Peng et al, from Taiwan [21]. In addition, they found that complete virological response at 6 months is a favorable predictive of HBeAg loss at 2 years of Entecavir therapy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…During TDF treatment, non-detectable serum HBV DNA at week 24 is the strongest predictor for an optimal response at 2 years (19). Similar results have been reported with ETV therapy (20). Based on the evidence supporting, the predictive value of on-treatment kinetics, a 'road map' algorithm of practical guidelines recommending HBV DNA measurements at weeks 12 and 24 has been proposed (21).…”
Section: Monitoring Therapymentioning
confidence: 64%
“…Furthermore, recent studies have suggested that earlier suppression of the HBV DNA to an even lower level during the course of antiviral therapy has a higher likelihood of resulting in improved clinical outcomes [15]. For example, the highest rates of HBeAg seroconversion and lowest rates of drug resistance were observed in a subgroup of patients who achieved serum HBV-DNA levels \2000 IU/mL within the first 6 months of lamivudine (LAM) treatment [16].…”
Section: Introductionmentioning
confidence: 99%